QUALITY ASSESSMENT OF ORGANIC MENTIK SUSU AND NON-ORGANIC CIHERANG RICE IN CANDIPURO, SOUTH LAMPUNG - Handayani, Sri; Zaini, Muhammad; Oktaviani, Anggita Dwi; Marbudi (Fakultas Pertanian dan Bisnis, Universitas Kristen Satya Wacana, 2025)
Rice quality plays an important role in determining market value and consumer preference, particularly as organic rice gains popularity for its health and environmental benefits. This study aimed to evaluate and compare the physical quality of organic Mentik Susu rice and non-organic Ciherang rice according to the Indonesian National Standard (SNI 6128:2015). The research was conducted at the Quality Laboratory of Politeknik Negeri Lampung in August 2025. The analysis involved assessing head rice, broken rice, brewers, damaged grains, chalky grains, colored grains, foreign materials, and unhulled grains. The results showed that both rice varieties met the general requirements for quality rice, with no presence of pests, foreign odors, bran contamination, or harmful chemicals. Based on specific parameters, Mentik Susu met seven out of eight criteria for premium-grade quality, except for head rice, which fell slightly below the 85 percent minimum threshold and was classified as Medium I. In contrast, Ciherang met the Medium I category for several parameters but did not meet the standard for broken rice and brewers due to exceeding maximum limits. The findings indicate that Mentik Susu organic rice has better grain integrity and physical quality compared to Ciherang, although both require improved post-harvest handling-especially during drying and milling, to meet the premium standard. These results highlight the importance of optimizing cultivation and post-harvest management to enhance the competitiveness of local rice varieties in the premium market.